Work, Education and Human Emancipation Humana: Affirming Youth and Adult Education as a right - Fischer, Maria Clara Bueno; Godinho, Ana Cláudia Ferreira (Education Policy Analysis Archives, 2014)
This article discusses the Education of Youth and Adults in Brazil as a right and as a field of studies and political intervention with practices and reflections of distinct or even antagonistic political-pedagogical bases. Such reflections are part of the debate on the fundamentals and forms of relationship between education, work and human emancipation. A key argument of the text is the conviction that young and adults are subjects of rights and the fulfillment of one of them - access and permanence in school - depends on the (re) cognition, by all those involved in the field, of the nature and the potential of the relationship of these subjects to the worlds of work. In this qualitative study, the authors conducted document analysis and data from two qualitative educational researches. The data was taken through semi-structured interviews, participant observation and field work notes. It was argued on the centrality of singular and collective experience of student-worker to mediate relations between work and education in the curriculum of youth and adult education. The authors emphasize the work as a place where workers make permanent production, mobilization and ( re) interpretation of knowledge and values. They put into circulation in the school context this knowledge and values of their working experience, generating tensions that drive the rapprochement between school knowledge and work experience. The authors emphasize the relevance of new studies on the Integrated Curriculum and other curricular practices that enhance the work as a singular and fundamental human experience.